Pengaruh Edukasi Stunting Terhadap Pengetahuan dan Sikap Ibu Bayi dalam Pencegahan Stunting di Posyandu Kaca Piring - Yeti Trisnawati (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2022)
ABSTRACT Background: Stunting is a dangerous nutritional problem today because it affects the future of children to adulthood. In Tanjungpinang City, the prevalence of stunting in Tanjungpinang in 2018 was very high, at 25.28%. Parents, especially mothers, have a very important role in fulfilling children's nutrition. The mother's low knowledge and attitude towards stunting prevention can have an effect on increasing the incidence of stunting in toddlers. For this reason, various health efforts need to be carried out to reduce the incidence. The purpose of this study was to determine the effect of stunting education on mother's knowledge and attitudes in preventing stunting at the Kaca Piring Posyandu in the Working Area of the Malay Health Center in Piring City, Tanjungpinang City. Method: The research method used a quasi experimental one group pretest-posttest design. The population is mothers who have babies aged less than 1 year. Samples were taken by 18 respondents by accidental sampling. The provision of education with the audiovisual method is approximately 1 hour. Assessment of pretest and posttest with a questionnaire instrument. Test the analysis using paired t-test. Result: The results showed that the mean difference between the pretest and posttest on the knowledge variable was 4.17 with a p value of 0.001, while the attitude variable showed that the mean difference between the pretest and posttest was 8.78, with a p value of 0.001. This shows that there are significant differences in knowledge and attitudes before and after stunting education. It was concluded that stunting education was effective in increasing the knowledge and attitudes of mothers with toddlers in stunting prevention. Efforts are needed to provide continuous understanding so that mothers better understand the problem of stunting and its prevention, especially in providing nutritious food. Keywords: education, stunting, baby's mother